Sikap Masyarakat Muslim Kota Medan Terhadap Kedudukan Anak Angkat - Adilla Putri Putri; Muhammad Faisal Hamdani; Imam Yazid (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The Muslim community of Medan city, which adopts children, punishes adopted children like biological children. This study aims to determine the position of adopted children in the view of Islam, to determine the attitude of the Muslim community of Medan City towards the work of adopted children, and to analyze the perspective of the Muslim community of Medan City on the position of adopted children in terms of Law no. 23 of 2002, Compilation of Islamic Law and applicable regulations. To answer these problems, field research was conducted with a qualitative research analysis model, which was analyzed through national law theory, Islamic law, and adat law. Based on the study results, it is known that the attitudes of the Muslim community in the city of Medan to the position of adopted children vary. Some people make the position of adopted children like biological children. But some people understand the position of adopted children so that they do not equalize their position as biological children.